2016
DOI: 10.1542/peds.2015-1948
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes From Polyhydramnios With Normal Ultrasound

Abstract: OBJECTIVE: To investigate the short-and long-term outcomes of children from pregnancies complicated with polyhydramnios, defined as amniotic fluid index (AFI) >24 cm, and with a normal detailed ultrasound examination. METHODS:This retrospective cohort study examined 134 children aged 4 to 9 years with polyhydramnios and normal detailed ultrasound examination during pregnancy compared with 268 controls with normal AFI and normal detailed ultrasound examination matched for maternal age, year of delivery, gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 26 publications
5
26
2
6
Order By: Relevance
“…In comparison with other studies [12,13] we observed fewer cases of diabetes in patients with polyhydramnios, most of them in the group with moderate polyhydramnios and only one in women with severe one. This result might be explained by better metabolic control in our diabetic group.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In comparison with other studies [12,13] we observed fewer cases of diabetes in patients with polyhydramnios, most of them in the group with moderate polyhydramnios and only one in women with severe one. This result might be explained by better metabolic control in our diabetic group.…”
Section: Discussioncontrasting
confidence: 82%
“…This result might be explained by better metabolic control in our diabetic group. Although the incidence of diabetes was approximately 10% in patients with polyhydramnios, it was approximately 20.9% and 14.9%, respectively, as observed by Yefet et al [13] and Boito et al [12].…”
Section: Discussionmentioning
confidence: 64%
“…At the beginning, we would like to answer the question: does the normal weight of the child or its disorders, such as SGA or macrosomia accompanying idiopathic polyhydramnios may be a prognostic factor of abnormalities after delivery? The percentage of fetuses with macrosomia in our study was 12.5% (8/64) and was similar to the results obtained by Yefet [8]. Yefet showed a statistically significant relationship between fetal macrosomia and idiopathic polyhydramnios, and compared the outcome to the control group without polyhydramnios (11% vs. 5%).…”
Section: Discussionsupporting
confidence: 90%
“…The percentage of genetic defects estimated in our study was 3.1%. This result is similar to the outcomes obtained by Yefet et al (3.7%) and the meta-analysis published in 2015 [8,11]. On the basis of the analysis of 1729 pregnancies with polyhydramnios of the unknown etiology, Sagi-Dain estimated the risk of chromosomal aberration at 2.8 ± 3.7%.…”
Section: Discussionsupporting
confidence: 89%
“…Up to 2% of all pregnancies have an excess amount of fluid meeting the criteria for polyhydramnios[1,2]. It is reported in the literature that approximately sixty percent of polyhydramnios is idiopathic; twenty percent of polyhydramnios can be attributed to poorly controlled or undiagnosed diabetes and the remainder of cases of polyhydramnios are associated with fetal anomalies[2-4]. Several adverse outcomes have been associated with polyhydramnios including preterm labor and rupture of membranes.…”
Section: Introductionmentioning
confidence: 99%